Building a Quality Curriculum: Optimizing the Curriculum Management Process in Madrasah Aliyah - Setyaningsih, Rini; Kuswanti, Adlia; Iskandar, Edi (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Optimizing curriculum management is a strategic step in supporting the success of superior education programs at Madrasah Aliyah Negeri 1 Pekanbaru. This study is motivated by the importance of implementing effective curriculum management to improve the quality of education, especially in the aspects of planning, development, implementation, and evaluation. This study aims to analyze the optimization of the curriculum management process at the madrasah. The approach used is qualitative with a case study design. Data collection techniques through direct observation and in-depth interviews. Data were collected from 2 people, namely the head of curriculum and teachers, then analyzed using data reduction, data presentation, and drawing conclusions. The results of the study indicate that curriculum planning is carried out collaboratively by involving various stakeholders to ensure alignment with student needs and the vision of the madrasah. Program implementation is closely monitored through routine supervision, with significant improvements in curriculum implementation based on the results of this supervision. Curriculum evaluation is carried out comprehensively, using learning outcome data and input from various parties, such as supervisors and senior teachers, who make important contributions to program improvement. The development of superior education programs focuses on the integration of religious values, academic enrichment, and the addition of relevant extracurricular activities to support student development holistically. This study concludes that optimal curriculum management plays a significant role in supporting the success of the curriculum and superior education programs. The implications of this study are the need for increased training for teachers and curriculum staff, as well as strengthening data-based evaluation systems to maintain the sustainability of superior education programs.